Porous Penality and the Myth of Liberal Punishment: Lessons from South Africa - Super, Gail (The British journal of criminology, 2024)
Drawing on Walter Benjamin, this paper discusses the relationships between law, violence, and punishment. The main argument I make is that state punishment is BOTH a violent and logically contradictory practice and that the state’s legal right to punish often spills over into extralegal penal violence, perpetrated by a range of actors against the racialized poor. I use the term penal violence to refer to all forms of violence which are aimed at enforcing law or punishing a perceived transgression of law or norms. The paper focuses on the infliction of penal violence in South Africa on/in three different scales and jurisdictions: Makwanyane and violence in prisons; police and prosecutorial violence; and extralegal civilian violence.